Corruption and Anticorruption: The Case of India. Issue 1 (March 2016) - Riley, Parkes; Roy, Ravi K.
India is corrupt, but according to Transparency International, it is less so than it used to be and less so than many similar countries. People often blame India's corruption on the system of business licensing that prevailed from the 1950s through the 1980s, but Pakistan, even without such a system, has been rated higher in corruption. Significantly, India's nationalist movement was often moralistic, especially because of the influence of Mahatma Gandhi. Gandhian traditions have lingered and affected anticorruption drives in 1974–1975 and in 2011 and after. Corruption continues in India for several reasons, including ingrained habits, the pervasiveness of the government, the opportunities for crony capitalism that have come with liberalization, and a loss of civic faith. At least in its more obvious forms, corruption may slowly fade, because India does have civic traditions, and because there is a revulsion against it that has inspired both protest activities and electoral campaigns.